Abnormal Admission Chest X-Ray and MEWS as ICU Outcome Predictors in a Sub-Saharan Tertiary Hospital: A Prospective Observational Study - Hannington Ssemmanda; Tonny Stone Luggya; Clare Lubulwa; Zeridah Muyinda; Pascal Kwitonda; Humphrey Wanzira; Joseph Ejoku (Critical Care Research and Practice)
Background. Critical care in Uganda is a neglected speciality and deemed costly with limited funding/prioritization. We studied admission X-ray and MEWS as mortality predictors of ICU patients requiring mechanical ventilation. Materials and Methods. We did a cross-sectional study in Mulago Hospital ICU and 87 patients for mechanical ventilation were recruited with mortality as the outcome of interest. Chest X-ray results were the main independent variable and MEWS was also gotten for all patients. Results. We recruited 87 patients; most were males (60.92%), aged between 16 and 45 years (59.77%), and most admissions for mechanical ventilation were from the Trauma Unit (30.77%). Forty-one (47.13%) of the 87 patients died and of these 34 (53.13%) had an abnormal CXR with an insignificant IRR = 1.75 (0.90–3.38) (p=0.062). Patients with MEWS ≥ 5 (p values = 0.018) and/or having an abnormal superior mediastinum (p values = 0.013) showed a positive association with mortality while having a MEWS ≥ 5 had an incidence risk ratio = 3.29 (1.00–12.02) (p=0.018). MEWS was a good predictor of mortality (predictive value = 0.6739). Conclusion. Trauma (31%) caused most ICU admissions, having an abnormal admission chest X-rays positively associated with mortality and a high MEWS was also a good predictor of mortality.